Stiffened steel box columns. Part 1 Cyclic behaviour. - Ge, Hanbin (Earthquake engineering & structural dynamics.)
This paper aims to study the cyclic inelastic behaviour of stiffened steel box columns failed by local and overall interaction instability under a constant compressive axial force and cyclic lateral loading. Such columns find broad application in steel bridge piers. The columns are of box sections with longitudinal stiffeners. In the analysis, a modified two surface plasticity model developed at Nagoya University is employed to model material non-linearity. For comparison, analyses using classical isotropic and kinematic hardening models are also carried out. Hysteretic curves and buckling modes obtained from analysis using the two surface model and classical models are compared with experimental results. Moreover, the progression of deformation from occurence of local buckling to structural failure is discussed in detail. The comparisons show that the use of an accurate plasticity model is quite important in the prediction of both the cyclic inelastic behaviour and failure characteristic of steel box columns failed by coupled local and overal instability. It is found that the modified two surface model is a satisfactory model in predicting the cyclic hysteretic behaviour of both the thin and thick walled steel box columns.